Analysis of the use of acronyms and initialisms as cultural referents in medical texts - Betancourt Ynfiesta, Beatriz; Treto Suárez, Lorena (Universidad Central “Marta Abreu” de Las Villas, 2011)
Taking into account that the translation of acronyms and initialisms is not only language-dependent, but also culture-bound, the aim of this study is to analyze the translation procedures used to translate into Spanish acronyms and initialisms used in English medical texts on Cardiology. This study attempts to present a theoretical and practical stand on the issue under research. It is a qualitative, interpretive, descriptive, synchronic study based on the lexical analysis of acronyms and initialisms in the English ST and the Spanish TT within the framework of descriptive translation studies. This is the first time the issue of translating acronyms and initialisms as cultural referents in specialized texts is tackled in the English Language Department. Thus, this study will deepen existing knowledge on how to deal with acronyms and initialisms, as forms of cultural referents, in medical texts. The study will hopefully contribute to the ongoing efforts aiming at improving translation in general, and translation of medical texts in particular.
Keywords: Literatura Inglesa/Estudio y Enseñanza; Acronyms; Translation Procedures; English Medical Texts; Spanish Acronyms; Initialisms; Cultural Referents